THE DEVELOPMENT OF COGNITIVE STYLISTICS - Ganieva Z. M. (Galaxy International Interdisciplinary Research Journal, 2023)
This article is about the introduction and development of Cognitive Stylistics which is one of the most modern trends of Cognitive Linguistics. Article defines what is Cognitive Stylistics and the difference between it and traditional stylistics. Moreover, in the article there has been a try to identify some problems that cover Cognitive Stylistics.